Livestock, capture fisheries, and aquaculture in Myanmar: Status and recent trends - Belton, Ben; Fang, Peixun (International Food Policy Research Institute, 2022)
Traditional forms of livestock-rearing and fishing have been central components in rural livelihoods in Myanmar for centuries and remain important today. More capital-intensive forms of marine fishing, aquaculture, and poultry farming began to expand during the early-1990s and grew briskly thereafter. This paper summarizes the status of the supply side of livestock, capture fisheries and aquaculture sectors in Myanmar, based on analysis of nationally representative data extracted from the Myanmar Living Conditions Survey 2017 and supporting information from other recent surveys and secondary sources. We examine levels of livestock ownership, participation in capture fisheries and aquaculture, reasons for rearing livestock, ownership of fishing assets, and household earnings from all three activities. We also discuss the characteristics of more geographically clustered, capitalintensive forms of poultry and swine farming, fishing, and fish farming, and the downturn in these sectors beginning in 2020 with the twin crises of COVID-19 and the coup. We conclude with a discussion of possible future directions for livestock farming, capture fisheries and aquaculture in Myanmar, along with priorities for sectoral upgrading.